Analysis On Study Address Terms and Gender Dyanamic Found In Mambalan: A Pragmatic Study - Miswaty, Titik Ceriyani; Sugianti, Linda; Arsinabila, Oyi (Jurnal Ilmiah Mandala Education (JIME), 2025)
Address terms and politeness strategies play a crucial role in communication, reflecting social relationships, cultural norms, and gender dynamics. This study investigates the use of address terms in Mambalan, a village in West Nusa Tenggara, Indonesia, within the context of Sasaknese language, gender roles, and sociocultural influences. Address terms in Mambalan are shaped by age, class, and relational context, demonstrating an interplay between traditional values and modernization. The research draws on Brown and Levinson's politeness theory, focusing on strategies such as positive and negative politeness to explore how language maintains social "face" and harmony. The study reveals how gender influences conversational patterns, with men predominantly using apologies and expressions of obedience, while women frequently use questions to sustain interaction. These gendered language choices reflect societal expectations and power dynamics, underscoring the role of politeness in reinforcing social cohesion. The research contributes to a deeper understanding of language use in multilingual, stratified societies and offers insights into how address terms can illuminate gendered communication patterns, identity, and cultural change.